Characteristics of tram wheel wear: Focus on mechanism identification and surface topography. (October 2020) - Wojciechowski, Ł.; Gapiński, B.; Firlik, B.; Mathia, T.G.
Abstract: The increasing development of tram networks and the growing use of urban rail rolling stock generates the need to look for solutions to maximise their durability and reliability. From a tribological point of view, particularly the relationship between motion and friction, the wheel-rail contact of the tram is of special importance. Therefore, the first purpose of this study was the identification of the wear mechanism on tram wheel tyres as a starting point to identify ways to increase their wear resistance in the future. Subsequently, a detailed analysis of the surface topography of the worn surfaces of tyres, in the context of wear processes, was made. This part of the investigation included the analysis of both height parameters of roughness (ISO 25178) and Abbott-Firestone curves, with their characteristics (ISO 13565). In addition, their correlation with operational factors such as axial load and mileage was examined. Based on this investigation, specific roughness parameters particularly predisposed to tracking and identifying early signs of wear, have been selected and proposed. Highlights: Shelling was recognised as the dominant wear mechanism of the tram wheel tyres. Post-shelling material losses are locations where abrasive and adhesive wear may appear. Surface topography measurements show high potential in identifying the wear of tram wheel tyres. Parameters describing the core and peak part of roughness are strongly correlated with the axle load and mileage. The geometry of surface valleys are at a similar level when signs of rolling contact fatigue are observable.